Structural Stigma and Sexual Minority Victimization Across 28 Countries: The Moderating Role of Gender, Gender Nonconformity, and Socioeconomic Status - Bränström, Richard (Journal of interpersonal violence, 2023)
Objective:Country-level structural stigma toward sexual minority individuals (i.e., discriminatory laws and policies and prejudicial attitudes) shows robust associations with sexual minority individuals’ mental health and individual-level stigma processes, such as identity concealment. Whether structural stigma is also associated with interpersonal-level stigma processes, such as victimization, is rarely studied. Whether the association between structural stigma and sexual minority individuals’ interpersonal mistreatment varies across gender, gender nonconformity, and socioeconomic status also remains to be determined.Methods:In 2012, sexual minority adults (n = 86,308) living in 28 European countries responded to questions assessing past-12-month victimization experiences (i.e., physical or sexual attack or threat of violence). Country-level structural stigma was objectively indexed as an aggregate of national laws, policies, and population attitudes negatively affecting sexual minority individualsResults:Country-level structural stigma was significantly associated with victimization (adjusted odds ratios [AOR]: 1.13, 95% confidence interval [CI]: 1.04–1.22; p = .004). However, this effect varied by gender, gender nonconformity, and socioeconomic status. For both sexual minority men and women, gender nonconformity and lower socioeconomic status were associated with increased risk of victimization. The strongest association between country-level stigma and victimization was found among gender nonconforming men with lower socioeconomic status (AOR: 1.32, 95% CI: 1.14–1.52; p < .001).Conclusions:A much larger proportion of sexual minorities living in higher stigma countries reports victimization than those living in lower stigma countries. At the same time, the association between country-level structural stigma and victimization is most heavily concentrated among gender nonconforming men with lower socioeconomic status.